A solid-state power amplifier for W band airtight application - Yu Xiaohui; Feng Sirun; Ma Zhangang (Dianzi Jishu Yingyong)
In order to meet the power combination requirements of 3 mm band， a novel 8 in 1 high power amplifier， which works at watt level for W band use， is proposed. It achieves module airtightness by utilizing silicon based chips， which is an innovative way for W-band waveguides. The conbiner design is based on the waveguides and the electromagnetic analysis is conducted for the inner structures. High frequency simulating softwares are also used to simulate the power combiner. By comparing the tested results and simulated indicators， this W-band power amplifier based on airtight waveguides can meet all the design requirements.